Detection of COVID-19 vaccine rejection situation and reasons in people over 18 years of age applying to family health centers in Karabük and its relationship with health literacy level - EKMEKCİ, Gülşah Büşra; Nacar, Erkay; Arıcan, Ali Ayberk (Scientific Reports in Medicine, 2025)
AbstractObjective: The aim of this study is to examine the rejection of the COVID-19 vaccine, its reasons and its relationship with health literacy levels.Material and Method:  This study is a cross-sectional analytical study. The sample of the research consisted of 648 people who applied to family health centers in Karabük province between May 2022 and June 2022 and agreed to participate in the research. "Sociodemographic Characteristics", "Questions determining the characteristics of COVID-19 vaccine rejection" and "Health Literacy Scale TSOY-32 scale" were used to collect data. Descriptive characteristics of people are expressed with frequency and percentage in categorical data. Pearson Chi-Square and Fisher's Exact Test were used. A value of p
Keywords: COVID-19 vaccines; health literacy; vaccination refusal